Ob štiridesetletnici združitve Slovenskega Primorja s Slovenijo - Vrišer, Igor (Geografski vestnik, 1987)
The article presents the history of demarcation between Italy and Yugoslavia after the II. World war and later development of this area. It presents also some regional development problems: economic development, demographic conditions, industrialization, development of port Koper, construction of transport connections and deterioration environment quqlity.
Keywords: družbena geografija; geografija; geography; human geography; Slovenia; Slovenija; Slovensko primorje